Diagnostic value of pituitary volume in girls with precocious puberty - Su Wu; Yan Yang; Yujiao Wang; Qianqi Liu; Ziyang Zhu; Wei Gu (BMC, 2020)
Abstract Background To date, the gonadotropin-releasing hormone (GnRH) stimulation test is still the gold standard for precocious puberty (PP) diagnosis. However, it has many disadvantages, including low sensitivity, high cost, and invasive operation. This study aims to evaluate whether magnetic resonance imaging (MRI)-derived variables, including pituitary volume (PV), could be used as diagnostic factors for PP in girls, providing a non-invasive diagnostic approach for PP. Methods A total of 288 young female patients who presented to the Clinic of Pediatric Endocrinology for evaluation of PP from January 2015 to December 2017 were enrolled. The sample included 90 girls diagnosed with premature thelarche (PT), 133 girls determined as idiopathic central precocious puberty (ICPP), 35 early pubertal girls, and 30 normal girls. All patients received pituitary MRI examinations. Results The largest PV and pituitary height were shown in the ICPP and pubertal groups, followed by the PT group. The receiver operating characteristic (ROC) curve analysis showed that PV is a predictive marker for ICPP, with a sensitivity of 54.10% and a specificity of 72.20% at the cutoff value of 196.01 mm3. By univariate analysis, PV was positively associated with peak luteinizing hormone (LH), LH/follicle-stimulating hormone (FSH), age, bone age, and body mass index (BMI) (all P < 0.05). However, bone age and peak LH were the only significant predictors of PV as demonstrated by the stepwise multivariate regression analysis (Model: PV = 9.431 * bone age + 1.230 * peak LH + 92.625 [P = 0.000, R2 = 0.159]). Conclusions The PV in the ICPP group was significantly higher than in PT and control groups, but there was no reliable cutoff value to distinguish ICPP from PT. Pituitary MRI should be combined with clinical and laboratory tests to improve the diagnostic value of PV for PP.